Mycochemical Screening and Analysis, Antioxidant Activity, and Biochemical Composition of Fermentation Strain Snef1216 (Penicillium chrysogenum) - Aatika Sikandar; Mengyue Zhang; Yuanyuan Wang; Xiaofeng Zhu; Xiaoyu Liu; Haiyan Fan; Yuanhu Xuan; Lijie Chen; Yuxi Duan (Journal of Analytical Methods in Chemistry)
Antioxidants are the radical scavengers that inhibit peroxidation and other free-radical processes, which in return safeguard different organisms from various diseases attributed to radical reactions. Synthetic antioxidants inhibit free radicals, but they also have harmful side effects. However, mycochemicals of natural fungal origin are safe and best substitutes for harmful synthetic chemical antioxidants. The prime objectives of the study include appropriate qualitative and quantitative mycochemical screening, antioxidant potential, and chemical composition of Snef1216 (Penicillium chrysogenum). The study has used aluminium chloride colourimetric method, Folin–Ciocalteu reagent assay, and DPPH (1,1-diphenyl-1-picrylhydrazyl) for analysis of total flavonoid content and phenol content and antioxidant activity, respectively. However, the presence of biologically active compounds was screened through gas chromatography-mass spectrometry (GC-MS). Quantitative analysis demonstrated the existence of flavonoids, glycosides, flavones, saponins, phenols, and catecholic tannins excluding alkaloids, terpenoids, steroids, and gallic tannins. The outcomes exposed total flavonoid content and phenolic content in P. chrysogenum were 85.31 ± 1.23 mg·QE/g and 135.77 ± 1.14 mg·GAE/g, respectively. Snef1216 (P. chrysogenum) displayed the highest free-radical scavenging activity with 63.86% inhibition of DPPH. The analysis confirms that Snef1216 (P. chrysogenum) is an alternative source of natural antioxidants. The obtained data have provided the foundation for its use in agricultural, environmental, and pharmaceutical industries.